The mediating effect of 18F-FDG metabolism in right caudate between depressive symptoms and cognitive function in Alzheimer’s disease - Wang, Bojun; Cui, Chunlei; Chen, Yifan; Liang, Zhigang (Frontiers in Aging Neuroscience, 2024)
Purpose: The objective of this study was to investigate the accumulation of 18F-Fluorodeoxyglucose (18F-FDG) in the whole brain between Alzheimer’s disease (AD) with depressive symptom (ADD) compared with AD without depressive symptom (ADND) using positron emission tomography/magnetic resonance imaging (PET/MRI), and to explore the associations among the accumulation of 18F-FDG in brain, depressive symptoms and cognitive function in ADD patients. Methods: 25 AD patients and 22 healthy controls were enrolled in this study. AD patients were divided into ADD and ADND groups based on the scores of the Hamilton Depression Scale (HAMD). Both AD patients and healthy controls underwent a 18F-FDG PET/MRI scan. Standardized uptake value ratio (SUVR) was calculated to examine brain accumulation of 18F-FDG. The simple mediation model was performed for the examination of the mediation effect between SUVR, depressive symptoms and cognitive function in ADD patients. Results: The ADD group exhibited significant cognitive impairment compared with the ADND group (p < 0.001) and healthy controls (p < 0.001). ADD patients exhibited the reduced SUVR (0.228±0.126) in the right caudate (the voxel level p < 0.005, cluster level p < 0.05, after false discovery rate (FDR) corrected compared with ADND group (0.459±0.064) and healthy controls (0.706±0.122). The SUVR of the right caudate was correlated with the HAMD scores (r = -0.792, p < 0.001) and Mini-Mental State Examination (MMSE) (r = 0.738, p < 0.01). Right caudate SUVR mediated the relationship between depressive symptoms and the cognitive function in ADD patients (total effects = -0.385, direct effects = -0.02, total indirect effects = -0.405). Conclusion: ADD group exhibited the reduced SUVR in the right caudate compared to ADND group and healthy controls. Right caudate SUVR mediated the relation of depressive symptoms and the cognitive ability of AD patients. The results deepen the understanding of the neurobiological mechanisms related to AD with depressive symptoms.